Towards an Orthodox Marxian Reading of Subsumption(s) of Academic Labour - Krystian, Szadkowski (My University, 2016)
This paper deploys an orthodox Marxian reading of the concept of subsumption of labour under capital. It does so through a brief, critical overview of the components of the Marxian conceptual instrument of subsumption of labour under capital (formal, real, hybrid and ideal subsumption). Recapitulating Marx’s concept, it sheds some light on the consequences of such a reading as a way of understanding the current transformation of the global higher education sector into a capitalist production sector per se. The reconstruction is then considered here as an attempt to approximate the specifics of the subsumption of labour under capital within the higher education sector. Moreover, the paper aims at showing that a discussion of the university dominated by capital with reference to the functioning or constituting of markets does not provide real opportunities for the understanding and solution of such problems as precarization, exploitation or acceleration of academic work. Thus, it joins a wider stream of Marxist higher education research and could be seen as a conceptual contribution to a critique of the political economy of higher education.
Keywords: higher education; Marxism; critical university studies; subsumption; Academic Labour